ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI TINGKAT PERTUMBUHAN EKONOMI SULAWESI SELATAN - Asdar Asdar (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2018)
This study aims: (1) to know and analyze the influence of labor on the economic growth of south sulawesi in 2005-2014. (2) to know and analyze the influence of goverment expenditure on economic growth of south sulawesi in 2005-2014. and (3) to know and analyze the influence of export to economic growth of south sulawesi years of 2005-2014. To complete the data and references needed in the preparation of this research, then taken by way of library research. Data were analyzed by using multiple linear regression analysis method which is descriptive quantitative method to analyze data more than one research variable. The result showed that: (1) the workforce has a positive and insignificant effect on the economic growth of south sulawesi (2) government expenditure has a positive and significant effect on the economic growth of south sulawesi (3) export have negative and insignificant impact on the economic growth of south sulawesi.